Dengeki Daisy. Vol. 9 - Motomi, Kyousuke (Shojo beat manga., 2012)
"As Teru comes to terms with Kurosaki's past wrongdoings, Kurosaki searches for the culprit who is trying to resurrect the 'Jack Frost' virus he created. But when he learns that Teru might be in danger, will he keep his promise to leave her alone, or will the two be reunited?"--Page 4 of cover.